A sodium ion battery positive electrode material synthesized using Prussian blue compounds, preparation method and application

The energy density and cost of sodium ion battery were solved by synthesizing ferrocyangan Prussian blue compound sodium ion battery using sodium hexanitrocobaltate Na3(Co(NO2)6) solution. The problem of this paper achieves efficient electrochemical performance and simplified preparation process.

CN115312761BActive Publication Date: 2024-12-24GUANGZHOU UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210910009.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2024-12-24
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

The energy density of sodium ion batteries is difficult to exceed that of lithium ion batteries, and the cost of sodium ion batteries is relatively high, so low-cost, high-performance cathode materials need to be developed to meet the needs of large-scale applications.

Method used

The positive electrode material of Na3Co(Fe(CN)6)2 of sodium hexanitrocobaltate sodium (Co(NO2)6) was synthesized into the sodium ionic battery by sodium ionizing compound Na3Co(Fe(CN)6)2 of the ferrocyangan Prussian blue compound sodium ion battery, and prepared by specific solution preparation and stirring reaction methods. This material simplifies the process flow.

Benefits of technology

It improves the cycle stability of the material and the first-circle Coulomb efficiency, reduces the preparation cost, realizes a high proportion of sodium components of sodium ion batteries and an open three-dimensional spatial framework structure, and enhances the electrochemical performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115312761B_ABST
    Figure CN115312761B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery materials, and discloses a sodium ion battery positive electrode material synthesized using a Prussian blue compound, a preparation method and an application. The sodium ion battery positive electrode material is a ferrocyanide Prussian blue compound sodium ion battery positive electrode material (NCFCN) synthesized using a hexanitrosodium cobaltate Na3(Co(NO2)6) solution, and its molecular formula is expressed as follows: Na3Co(Fe(CN)6)2. Different from the simple superposition of two typical modification methods, the present invention adopts a simple method to synthesize the ferrocyanide Prussian blue compound sodium ion battery positive electrode material (NCFCN), which simplifies the process flow. The sodium ion positive electrode material of the Na3Co(Fe(CN)6)2 Prussian blue compound has a high proportion of sodium components, which can meet the sodium ions released during the charging process, thereby suppressing the degree of structural collapse, thereby improving the first-cycle coulomb efficiency of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to a sodium ion battery positive electrode material synthesized using a Prussian blue compound, a preparation method and an application thereof. Background Art

[0002] Among the many electrochemical energy storage methods, lithium-ion batteries with high quality and volumetric energy density have been widely used. Since the successful application of lithium-ion batteries in portable devices in the early 1990s, lithium-ion battery technology used in commercial hybrid vehicles, electric vehicles, mobile phones and other electronic devices has developed rapidly. However, the relatively scarce and unevenly distributed lithium resources have caused a significant increase in the cost of lithium-ion battery production and raw material preparation. Lithium-ion batteries have gradually failed to meet the current growing energy storage needs. Compared with lithium resources, sodium resources are the sixth most abundant element in the earth's crust, and almost unlimited sodium resources can be obtained through seawater. The physical and chemical properties of sodium ions are similar to those of lithium ions. The development of sodium-ion battery electrode materials can refer to the synthesis methods of electrode materials in lithium-ion batteries, the ion embedding mechanism and related characterization methods. The working principle of sodium-ion batteries is similar to the "rocking chair" working principle of lithium-ion batteries. The electrode materials are immersed in the electrolyte and separated by a porous diaphragm for rapid sodium ion transmission. The positive and negative electrode materials are separated by the diaphragm to prevent the materials from contacting and short-circuiting. During the charging process, sodium ions are deintercalated from the positive electrode material and combined with the negative electrode material to achieve energy storage. During the charge and discharge cycle, electrochemical redox reactions occur simultaneously on the surface of the positive and negative electrode materials to achieve the conversion of chemical energy into electrical energy. Therefore, the electrode material of the sodium ion battery determines the quality of the battery's electrochemical performance. Compared with the size of lithium ions, Its electrochemical potential (3.04V, Li+ / Li), the size of the sodium ion It is larger and has a lower electrochemical potential (2.71V, Na+ / Na). The energy density of sodium-ion batteries is difficult to exceed that of lithium-ion batteries. However, the use of high-performance and low-cost sodium-ion battery electrode materials and low-cost materials such as aluminum foil current collectors can effectively reduce the cost of sodium-ion batteries. Considering the large-scale application of battery energy storage systems, reducing battery costs is more important than simply increasing energy density. Currently, more and more research is focused on the development of low-cost electrode materials for use in sodium-ion batteries. The positive electrode material in sodium-ion batteries determines the energy density and manufacturing cost of the battery. Moreover, the potential difference between the positive and negative electrode materials determines the operating voltage of the battery. In recent years, a large number of studies have focused on the development of low-cost, high-performance, fast sodium ion embedding and good cycle stability positive electrode materials. Summary of the invention

[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a sodium ion battery positive electrode material synthesized using a Prussian blue compound, and a preparation method and application thereof.

[0004] The purpose of the present invention is achieved by the following technical solutions:

[0005] In the first aspect, the present invention provides a sodium ion battery positive electrode material synthesized using a Prussian blue compound, which is a ferrocyanide Prussian blue compound sodium ion battery positive electrode material (NCFCN) synthesized using a hexanitrosodium cobaltate Na3 (Co(NO2)6) solution, and its molecular formula is expressed as follows: Na3Co(Fe(CN)6)2.

[0006] In a second aspect, the present invention provides a method for preparing a sodium ion battery positive electrode material synthesized using a Prussian blue compound, comprising the following steps:

[0007] (1) dissolving potassium ferrocyanide in water to prepare potassium ferrocyanide solution A;

[0008] (2) dissolving sodium hexanitrocobaltate Na3 (Co(NO2)6) in an ethanol solution to obtain a solution B;

[0009] (3) Adding solution B to solution A under stirring, stirring for reaction, and obtaining mixture C;

[0010] (4) The mixture C is centrifuged and washed for more than three times, and the washed powder is dried to obtain a Prussian blue compound positive electrode material.

[0011] Preferably, in step (1), the concentration of ferrocyanide ions in the potassium ferrocyanide solution A is 0.8 to 1.2 mol / L.

[0012] More preferably, in step (1), the concentration of ferrocyanide ions in the potassium ferrocyanide solution A is 1.0 mol / L.

[0013] Preferably, in step (2), the mass fraction of the ethanol solution is 1%-60%.

[0014] Preferably, in step (2), the amount of the sodium hexanitrocobaltate is calculated based on a molar ratio of potassium ferrocyanide to sodium hexanitrocobaltate of 2:0.8-1.

[0015] Preferably, in step (2), the concentration of sodium hexanitrocobaltate in solution B is 0.8 to 1.2 mol / L.

[0016] More preferably, in step (2), the concentration of sodium hexanitrocobaltate in solution B is 1.0 mol / L.

[0017] Preferably, in step (3), the stirring speed is 200-400 rpm, the reaction temperature is 20-90° C., and the reaction time is 0.5-12 h.

[0018] More preferably, in step (3), the stirring speed is 300 rpm, the reaction temperature is 30-60° C., and the reaction time is 2-6 h.

[0019] Preferably, in step (4), the drying condition is drying at a temperature of 20 to 80° C. for 10 to 14 hours.

[0020] More preferably, in step (4), the drying condition is drying at 60° C. for 12 hours.

[0021] Preferably, in step (4), the detergent is deionized water, the centrifugal speed is 1000-12000 r / min, and the centrifugal time is 5-30 min.

[0022] More preferably, in step (4), the centrifugal speed is 9000 r / min and the centrifugal time is 10 min.

[0023] In a third aspect, the present invention provides an application of a sodium ion battery positive electrode material synthesized using a Prussian blue compound in a battery.

[0024] The beneficial effects of the present invention are:

[0025] 1. Different from the simple superposition of two typical modification methods, the present invention adopts a simple method to synthesize ferrocyanide Prussian blue compound sodium ion battery positive electrode material (NCFCN), which simplifies the process flow.

[0026] 2. The sodium ion positive electrode material of Na3Co(Fe(CN)6)2 Prussian blue compound has a high proportion of sodium content, which can meet the sodium ions released during the charging process, thereby inhibiting the degree of structural collapse and improving the first-cycle coulomb efficiency of the material.

[0027] 3. Na3Co(Fe(CN)6)2 Prussian blue compounds have an open three-dimensional spatial framework structure, which improves the cyclic stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0029] Figure 1 This is the SEM image of the sodium ion battery positive electrode material Na3Co(Fe(CN)6)2 prepared in Example 1 of the present invention.

[0030] Figure 2 This is the XRD diagram of the sodium ion battery positive electrode material Na3Co(Fe(CN)6)2 prepared in Example 1 of the present invention.

[0031] Figure 3 This is a graph showing the cycle performance test results of a button-type half-cell prepared using the sodium ion battery positive electrode material Na3Co(Fe(CN)6)2 prepared in Example 1 of the present invention.

[0032] Figure 4 This is a graph showing the rate performance test results of a button-type half-cell prepared using the sodium-ion battery positive electrode material Na3Co(Fe(CN)6)2 prepared in Example 1 of the present invention.

[0033] Figure 5 This is the EDS-Mapping diagram of the sodium ion battery positive electrode material Na3Co(Fe(CN)6)2 prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] In order to more clearly illustrate the present invention and have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0035] At present, three important sodium ion positive electrode materials have been extensively studied. The first positive electrode material is an oxide material of transition metals and sodium. This type of positive electrode material has a high specific capacity and working voltage. However, the irreversible phase change of the crystal structure of this type of positive electrode material during the charging and discharging process seriously affects the electrochemical performance of the positive electrode material. At the same time, most of these positive electrode materials cannot exist stably in the air, resulting in a large increase in storage costs. Another positive electrode material is a polyanion compound material. This type of compound positive electrode material has the advantages of stable structure, good safety performance and small volume change of crystal structure during circulation. At present, a large number of studies are focused on iron-based, manganese-based and vanadium-based polyanion compound positive electrode materials. The last positive electrode material is a Prussian blue analog material. This type of positive electrode material has a high working voltage, excellent cycle stability and rate performance. This patent invents a method for preparing a Prussian blue compound positive electrode material in a simple and efficient way.

[0036] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0037] The present invention is further described in conjunction with the following examples.

[0038] Example:

[0039] The sodium ion battery positive electrode material synthesized using Prussian blue compounds provided in an embodiment of the present invention is a ferrocyanide Prussian blue compound sodium ion battery positive electrode material (NCFCN) synthesized using sodium hexanitrocobaltate Na3(Co(NO2)6) solution, and its molecular formula is expressed as follows: Na3Co(Fe(CN)6)2.

[0040] The method for preparing a sodium ion battery positive electrode material synthesized by using a Prussian blue compound comprises the following steps:

[0041] (1) dissolving potassium ferrocyanide in water to prepare potassium ferrocyanide solution A;

[0042] (2) dissolving sodium hexanitrocobaltate Na3 (Co(NO2)6) in an ethanol solution to obtain a solution B;

[0043] (3) Adding solution B to solution A under stirring, stirring for reaction, and obtaining mixture C;

[0044] (4) The mixture C is centrifuged and washed for more than three times, and the washed powder is dried to obtain a Prussian blue compound positive electrode material.

[0045] In this embodiment, potassium ferrocyanide is first dissolved in an aqueous solution to prepare a metal salt solution A; sodium hexanitrocobaltate Na3 (Co(NO2)6) is dissolved in an ethanol solution to obtain a solution B; the ethanol content in the ethanol solution is 1-60%; the solution B obtained in step (2) is added to the solution A obtained in step (1) under stirring, the reaction temperature is 20-90°C, and the reaction is continued for 0.5-12h to obtain a mixture C; the mixture C obtained by the reaction in step (3) is centrifugally washed for more than three times, and the washed powder is dried at 25-80°C to obtain a Prussian blue compound positive electrode material, the detergent is deionized water, the rotation speed is 1000-12000r / min, and the time is 5-30min.

[0046] The following is a detailed introduction to the technical solutions under different ratios.

[0047] Example 1

[0048] See attached Figure 1-5, a preparation method of a sodium ion battery positive electrode material synthesized using a Prussian blue compound, comprising: dissolving potassium ferrocyanide in an aqueous solution to prepare a metal salt solution A; dissolving sodium hexanitrocobaltate Na3 (Co(NO2)6) in an ethanol solution to obtain a solution B, wherein the molar ratio of potassium ferrocyanide to sodium hexanitrocobaltate is 1.5:1; the ethanol content in the ethanol solution is 50%; adding the solution B obtained in step (2) to the solution A obtained in step (1) under stirring, the reaction temperature is 50°C, and the reaction is continued for 3 hours to obtain a mixture C; the mixture C obtained by the reaction in step (3) is centrifugally washed for more than three times, and the washed powder is dried at 60°C to obtain a Prussian blue compound positive electrode material, the detergent is deionized water, the rotation speed is 9000r / min, and the time is 20min.

[0049] Example 2

[0050] The preparation method is the same as that of Example 1, except that the molar ratio of potassium ferrocyanide to sodium hexanitrocobaltate is 1.4:1.

[0051] Example 3

[0052] The preparation method is the same as that of Example 1, except that the molar ratio of potassium ferrocyanide to sodium hexanitrocobaltate is 1.3:1.

[0053] Example 4

[0054] The preparation method is the same as that of Example 1, except that the molar ratio of potassium ferrocyanide to sodium hexanitrocobaltate is 1.2:1.

[0055] Experimental Example 5

[0056] The preparation method is the same as that of Example 1, except that the molar ratio of potassium ferrocyanide to sodium hexanitrocobaltate is 1.1:1.

[0057] Example 6

[0058] The preparation method is the same as that of Example 1, except that the molar ratio of potassium ferrocyanide to sodium hexanitrocobaltate is 1:1.

[0059] Experimental application examples

[0060] (1) Material characterization: The materials prepared in the examples were characterized by SEM. The results are as follows Figure 1 As shown in Figure 2, both have good Prussian type morphology. The example materials were characterized by XRD, as shown in Figure 2. Figure 2 As shown, the spectrum conforms to the characteristic peaks (200), (220), (400) and (420) of Prussian blue compounds, indicating that this method can synthesize good Prussian blue compounds.

[0061] (2) Battery assembly: The ferrocyanide Prussian blue compound sodium ion battery positive electrode material (NCFCN) prepared in the example was mixed with Super P (conductive carbon black) and PVDF (polyvinylidene fluoride) in a mass ratio of 8:1:1, slurried and coated, and then vacuum dried and cut into original sheets with a diameter of 10 mm. The half-cell was assembled with a metal sodium sheet as the negative electrode.

[0062] (3) Performance test: After activating the battery for one cycle at a rate of 0.1C (1C = 100 mAh / g), the half-cell assembled above was subjected to a cycle test at a rate of 1C in the voltage range of 1.5-4.2V. Figure 3 As shown, the sodium ion battery positive electrode material (NCFCN) prepared in Example 1 using sodium hexanitrocobaltate Na3 (Co (NO2) 6) solution to synthesize ferrocyanide Prussian blue compounds has an initial discharge capacity of 41.9 mAh / g at 1C, a cycle capacity of 36.5 mAh / g after 100 cycles, and a capacity retention rate of 87.11%, indicating that the sodium ion battery positive electrode material (NCFCN) prepared in the present invention using sodium hexanitrocobaltate Na3 (Co (NO2) 6) solution to synthesize ferrocyanide Prussian blue compounds has good retention rate and cycle performance. Figure 4 The discharge capacities of the ferrocyanide Prussian blue compound sodium ion battery positive electrode material (NCFCN) prepared in Example 1 using sodium hexanitrocobaltate Na3 (Co(NO2)6) solution at 0.1C, 0.5C, 1C, 3C, 5C and 10C are 50.5mAh / g, 36.8mAh / g, 28.1mAh / g, 23.8mAh / g, 18.9mAh / g and 74.7mAh / g, respectively; this indicates that the ferrocyanide Prussian blue compound sodium ion battery positive electrode material (NCFCN) prepared by the present invention has excellent rate performance.

[0063] The above embodiment of the present invention is different from the simple superposition of two typical modification methods. The present invention adopts a simple method to synthesize the ferrocyanide Prussian blue compound sodium ion battery positive electrode material (NCFCN), which simplifies the process flow. The sodium ion positive electrode material of the Na3Co(Fe(CN)6)2 Prussian blue compound prepared on the reverse side has a high proportion of sodium components, which can meet the sodium ions released during the charging process, thereby inhibiting the degree of easy collapse of the structure, thereby improving the first-cycle coulomb efficiency of the material.

[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A sodium ion battery positive electrode material synthesized using a Prussian blue compound, characterized in that: The sodium ion battery positive electrode material is a ferrocyanide Prussian blue compound sodium ion battery positive electrode material (NCFCN) synthesized using a sodium hexanitrocobaltate Na3 (Co(NO2)6) solution, and its molecular formula is as follows: Na3Co(Fe(CN)6)2.

2. A method for preparing a sodium ion battery positive electrode material synthesized using a Prussian blue compound as claimed in claim 1, characterized in that: The following steps are involved: (1) Dissolve potassium ferrocyanide in water to prepare potassium ferrocyanide solution A; (2) dissolving sodium hexanitrocobaltate Na3 (Co(NO2)6) in an ethanol solution to obtain solution B; (3) Add solution B to solution A under stirring, and stir to react to obtain mixture C; (4) The mixture C is centrifuged and washed for more than three times, and the washed powder is dried to obtain a Prussian blue compound positive electrode material.

3. The method for preparing a sodium ion battery positive electrode material synthesized using a Prussian blue compound according to claim 2, characterized in that: In step (1), the concentration of ferrocyanide ions in the potassium ferrocyanide solution A is 0.8 to 1.2 mol / L.

4. The method for preparing a sodium ion battery positive electrode material synthesized using a Prussian blue compound according to claim 2, characterized in that: In step (2), the mass fraction of the ethanol solution is 1%-60%.

5. The method for preparing a sodium ion battery positive electrode material synthesized using a Prussian blue compound according to claim 2, characterized in that: In step (2), the amount of sodium hexanitrocobaltate is calculated based on a molar ratio of potassium ferrocyanide to sodium hexanitrocobaltate of 2:0.8-1.

6. The method for preparing a sodium ion battery positive electrode material synthesized using a Prussian blue compound according to claim 2, characterized in that: In step (2), the concentration of sodium hexanitrocobaltate in solution B is 0.8 to 1.2 mol / L.

7. The method for preparing a sodium ion battery positive electrode material synthesized using a Prussian blue compound according to claim 2, characterized in that: In step (3), the stirring speed is 200-400 rpm, the reaction temperature is 20-90° C., and the reaction time is 0.5-12 h.

8. The method for preparing a sodium ion battery positive electrode material synthesized using a Prussian blue compound according to claim 2, characterized in that: In step (4), the drying condition is to dry at a temperature of 20 to 80° C. for 10 to 14 hours.

9. The method for preparing a sodium ion battery positive electrode material synthesized using a Prussian blue compound according to claim 2, characterized in that: In step (4), the detergent is deionized water, the centrifugal speed is 1000-12000 r / min, and the centrifugal time is 5-30 min.

10. Use of the sodium ion battery positive electrode material synthesized using the Prussian blue compound according to claim 1 in a battery.

Citation Information

Patent Citations

  • Phosphide nano catalyst and preparation method thereof

    CN109301267A

  • Prussian blue cathode material for sodium ion batteries and preparation method thereof and sodium ion battery

    CN109728292A